The Use of Kahoot Application as a Learning Media to Improve Students' Vocabulary Mastery in Seventh Grade SMP Negeri 1 Ciomas - maesaroh, Maesaroh; Juniardi, Yudi; Rahmawati, Dina (Universitas Muhammadiyah Tangerang, 2025)
The use of technology in education has become an integral component. This study aimed to investigate the effectiveness of the Kahoot application as a learning medium for seventh-grade students at SMPN 1 Ciomas in the academic year 2023/2024. The study employed a qualitative-quantitative approach through Collaborative-Classroom Action Research conducted in two cycles. The research sample consisted of 27 students from class VII E. Data were collected through participatory observation, pre-tests, post-tests, and closed questionnaires. Data analysis results indicated pre-test and post-test values at a significance level of 5% with degrees of freedom of 26 and a t-table value of 2.056, where the t-value for Cycle I was higher than the t-table (6.421 > 2.056) and for Cycle II was also higher than the t-table (9.593 > 2.056). Observations showed a significant increase in student participation levels, shifting from